Lectures on Shakespeare - Auden, W. H. (Wystan Hugh), 1907-1973 (Princeton classics., 2019)
"From one of the great modern writers, the acclaimed lectures in which he draws on a lifetime of experience to take the measure of Shakespeare's plays and sonnets. Reconstructed by Arthur Kirsch, these lectures offer remarkable insights into Shakespeare's plays and sonnets while also adding immeasurably to our understanding of Auden"--